Distribution Pattern of Volcanic Ash Essential Elements on the Top Layer of Agricultural Land Post Merapi Eruption in Sleman - Sri Murniasih; Darsono Darsono; Sukirno Sukirno; Saefurrochman Saefurrochman (Indonesian Journal of Chemistry, 2019)
Volcanic ash contains essential elements to the soil fertility of agricultural land which is important to be investigated. The aim of this study was to determine the distribution pattern of volcanic ash essential elements as a result of volcanic eruption disaster using Surfer software. To input, the Surfer software, soil samples of volcanic ash at 10 sampling locations in Sleman at a radius of 14 to 26 km towards the south from a peak of Merapi were collected. Data of wind direction, humidity and ground level at the time of sampling were also collected. The concentrations of the essential element in samples were measured using NAA (neutron activation analysis). The pH of volcanic ash samples in each sampling locations was also measured. The results showed that volcanic ash for all sampling locations contained, Al, Fe, Na, K, and Si as major elements and Zn, Co, and Se as trace elements. The concentration distribution pattern of the Zn, Si, Co and Fe elements tends to decrease towards the peak of Merapi, on the other hand, the Na, and K elements showed that their distribution concentration tends to decrease away from the peak of Merapi. The wind’s speed affects the distribution range of an element contained in volcanic ash samples. The pH of volcanic ash samples seemingly only affect the concentration of Zn elements in the distribution pattern of elements.